PADANGBULIA PEOPLE'S RESISTANCE TO PUBLIC POLICY NUMBER 10 OF 1951 CONCERNING THE ABOLITION OF THE MANAK SALAH TRADITION - Suraya, Rahmat Sewa; Rustiani, Komang Wahyu; Suardika, I Ketut (Sebatik, 2024)
In Bali, the birth of "kembar buncing," or mixed-gender twins, is often associated with negative connotations. Specifically, in Padangbulia, such births are traditionally accompanied by a ritual that includes the exile of the infants to a location deemed haunted by the local community. This practice of exile is a violation of human rights, leading to the issuance of Paswaran Number 10 of 1951, which mandates the abolition of the "Manak Salah" tradition. However, despite this regulation, the Padangbulia community continues to uphold the tradition. This study aims to explore the processes and forms of resistance by the Padangbulia community against the mandated abolition. The research adopts a qualitative descriptive approach, utilizing cultural semiotics and resistance theory to understand the community's actions. Data collection involved snowball sampling to select informants, supported by participant observation, interviews, and document analysis. Findings reveal that the "kembar buncing" tradition in Padangbulia involves several stages, including preparation, exile, and purification. The resistance to abolishing the tradition manifests both openly and covertly, highlighting the community's deep-seated cultural values and the complex dynamics between tradition and regulatory enforcement. This study sheds light on the persistence of traditional practices despite external pressures and the role of cultural resistance in maintaining local customs.